Comparison of Energetic Electron Fluxes Measured by GPS and THEMIS Spacecraft in the Inner Magnetosphere. Issue 10 (29th September 2022) - Curtis, Reed; Artemyev, Anton V.; Vainchtein, Dmitri L.; Kellerman, Adam; Morley, Steven K.; Angelopoulos, Vassilis
Abstract: Key elements of space weather models are energetic electron fluxes in the inner magnetosphere and the outer radiation belt. Flux depletion is driven by various loss processes: scattering into atmosphere, magnetopause shadowing. Flux enhancement is driven by various acceleration processes: local wave‐particle interactions, radial transport, plasma sheet injections. Many of these processes operate on ∼ hour timescales. Such mesoscale flux variations are not well traced by equatorial spacecraft with much longer orbits. Energetic electron detectors onboard the Global Positioning System (GPS) constellation provide a unique opportunity for probing such ∼ hour‐scale flux variations. Measurements from up to 23 identically instrumented GPS satellites cover a wide energy and L ‐shell range with a subhour time resolution. However, their orbits are inclined and thus all measurements at L ‐shell >4.3 are off‐equatorial. In this report, we present a comparison of equatorial THEMIS and nonequatorial GPS measurements of omnidirectional ≤600 keV electron fluxes. Such a comparison allows us to derive coefficients for using off‐equatorial GPS fluxes to infer the equatorial values. These coefficients depend on particle energy and L ‐shell. We demonstrate a new data set derived from GPS measurements and discuss how it can be used to investigate mesoscale dynamics of energetic electron fluxes in the inner magnetosphere. Key Points: Energetic electron fluxes measured by THEMIS have been compared to fluxes measured by GPS satellites Ratio of GPS and THEMIS fluxes for energies 100–600 keV has been fitted as a function of L ‐shell Projected GPS fluxes allows tracing the electron flux L ‐shell distributions with <1 hr time resolution